Sugar Free: Novel Immunotherapeutic Approaches Targeting Siglecs and Sialic Acids to Enhance Natural Killer Cell Cytotoxicity Against Cancer - Daly, John; Carlsten, Mattias; O'Dwyer, Michael (Frontiers in Immunology, 2019)
Natural Killer (NK) cells are cytotoxic lymphocytes that play a key role in the immune system, targeting and destroying invading pathogens and malignantly transformed cells. Evading NK cell-mediated immunosurveillance is therefore critical to facilitating cancer cell survival and metastasis. Signals from a range of inhibitory and activating receptors located on the NK cell surface regulate NK cell cytotoxicity. Recently, attention has turned to the role of hypersialylated tumor cell surfaces in mediating immune-evasion of NK cells. Two inhibitory sialic acid-binding immunoglobulin-like lectin (Siglec) receptors are expressed by NK cells: Siglec-7 and Siglec-9. The abundance of sialic acids on tumor cell surface is hypothesised to regulate NK cell-mediated cytotoxicity by interacting with Siglec-7 and Siglec-9, causing a dampening of NK cell activation pathways. Targeting Siglec-7 and Siglec-9, or the sialic acid coated tumor cell surface is therefore being investigated as a novel therapeutic approach to enhance the NK cell response against cancer. In this review we report on all currently published documentation of the role for Siglec-7 and Siglec-9 receptors on NK cells and their ligands expressed by tumor cells. We also discuss the strategies currently explored to target Siglec-7, Siglec-9 and the sialylated tumor cell surface as well as the impact abrogation of these interactions have on NK cell cytotoxicity against several cancer types.